Penatalaksanaan Fisioterapi Pada Post Op Rekonstruksi AnteriorCruciate Ligament Sinistra Grade III Akibat Ruptur Di RSPAD Gatot Soebroto - Santoso, Iman; Sari, Ikke Dwi Kartika; Noviana, Mita; Pahlawi, Riza (Jurnal Vokasi Indonesia, 2018)
Therefore the role of physiotherapy is very important in optimizing the motion and function in patients with post op reconstruction Anterior Cruciate Ligament sinistra Grade III due to Rupture. Physiotherapy may begin on the first day after reconstruction, the exercises being performed depending on the phases based on the day after reconstruction of the Anterior Cruciate Ligament rupture are performed.Based on the above explanation, the authors raised cases after reconstruction of Anterior Cruciate Ligament rupture as the final task implementation. The case discussed is the condition of a patient of Post Op Reconstruction Anterior Cruciate Ligament Sinistra Grade III due to Rupture at Central Hospital of Gatot Subroto.